Carboniferous-Early Permian heterogeneous distribution of porous carbonate reservoirs in the Central Uplift of the South Yellow Sea Basin and its hydrocarbon potential analysis - Shu-yu Wu; Jun Liu; Jian-wen Chen; Qi-liang Sun; Yin-guo Zhang; Jie Liang; Yong-cai Feng (China Geology, 2025)
ABSTRACT: Mesozoic-Palaeozoic marine carbonate rocks are crucial hydrocarbon reservoirs in the Central Uplift area of the South Yellow Sea Basin (SYSB). Due to the scarcity of boreholes and the significant heterogeneity of carbonate reservoirs, the distribution of porous carbonate reservoirs and their related key controlling factors remain unclear. In this study, factors affecting the distribution of porous Carboniferous-Early Permian carbonate reservoirs in the SYSB were investigated through seismic inversion and isotope analysis. The log-seismic characteristics of porous carbonate reservoirs, sensitive lithology parameters, and physical property parameters were extracted and analyzed. The pre-stack simultaneous inversion technique was applied to predict the lithology and physical properties of porous carbonate reservoirs. Moreover, the sedimentary of carbonate was analyzed using isotopes of carbon, oxygen, and strontium. The results show that porous carbonate reservoirs are mainly developed in the open platform sediments with porosities of 3%–5% and are mainly distributed in the paleo-highland (Huanglong Formation and Chuanshan Formation) and the slope of paleo-highland (Hezhou Formation). The porous carbonate reservoirs of the Qixia Formation are only locally developed. In addition, the negative δ13C excursions indicate a warm and humid tropical climate with three sea-level fluctuations in the study area from the Carboniferous to Early Permian. The favorable conditions for developing porous carbonate rocks include the sedimentary environment and diagenetic process. The primary pore tends to form in high-energy environments of the paleo-highland, and the secondary pore is increased by dissolution during the syngenetic or quasi-syngenetic period. According to the hydrocarbon potential analysis, the Late Ordovician Wufeng Formation and Lower Silurian Gaojiabian Formation are the source rocks in the high-maturity-over-maturity stage, the Carboniferous-Lower Permian carbonate is the good reservoirs, and the Late Permian Longtan-Dalong Formation is the stable seal, ensuring a huge hydrocarbon accumulation potential in SYSB. The methods proposed in this study can be applied to other carbonate-dominated strata worldwide.